Economic Empowerment of Indonesian Migrant Workers in Hong Kong Through Digital-Based Financial Literacy - Prajanti, Sucihatiningsih Dian Wisika; Kurniawan, Edi; Widiatningrum, Talitha (Universitas Negeri Semarang, 2025)
Many migrant workers in Hong Kong struggle to manage their income due to low levels of financial literacy, resulting in their economic potential not being optimally utilized. Low financial management skills can increase the risk of excessive debt and unproductive consumption, thus affecting their long-term welfare. The activities carried out in this service include Coordination of Service Implementation, Socialization, Digital-based Financial Literacy Training, and Mentoring. The implementation method used in this community partnership program is participatory. The results of the service showed an increase in understanding of financial literacy by 32%, and skills in using digital financial applications increased by 41%. In addition, this mentoring also strengthens social relationships between participants, local facilitators from PCIA Hong Kong, and the implementation team.